An investigation into the impact of diapir structures on formation pressure systems: a case study of the Yinggehai Basin, China - An Jintao; Li Jun; Honglin Huang; Hui Zhang; Hongwei Yang; Geng Zhang; Sainan Chen (Geothermal Energy)
Abstract Under the influence of diapir structure, the formation pressure system is complicated. The characteristics of high temperature and high pressure are obvious, the prediction is difficult, and complex accidents such as well kick and leakage are frequent, which seriously restrict the efficient development of oil and gas resources. Therefore, taking Yinggehai Basin in China as an example, combined with the evolution characteristics of diapir structure, the influence of diapir structure on abnormal high-pressure, wellhole collapse and fracture is analyzed. Three pressure calculation methods are selected, and the distribution rules of pressures and safety density window are analyzed, too. The results show that the diapir structure and its associated fault not only constitute the fluid transport system, but also make the deep overpressure transfer upward and accumulate into high pressure in the shallow formation, and the development of the associated fault destroy the integrity of the formation rock and reduce the strength of the rock. The upwelling of hot fluid changes the local geothermal conditions, reduces the hydrocarbon generation threshold of shallow source rocks, promotes the evolution of clay minerals, causes hydrothermal expansion, and enhances the shallow high pressure. In high-temperature environment, the cooling effect of drilling fluid will produce heating stress, change the stress distribution around the wellhole, and increase the risk of wellbore instability. Additionally, under the influence of diapir structures, the pore pressure in deep formations increases, while the fracture pressure decreases, resulting in a significantly narrowed safe density window. The safety density window width generally presents a half-spindle shape, and with the increase of depth, the window width increases first and then decreases.